Application of Learning Videos and Quizizz in Increasing Students Interest in Learning English in Middle Schools - Fadillah, Ine Nur; Maryanti, Rina (Indonesian Journal of Multidiciplinary Research, 2021)
The government's policy towards the education sector during the pandemic by imposing Distance Learning is still experiencing many obstacles. Many students have difficulty understanding the concept of monotonous lessons and learning so that students become bored and lose interest in learning. This study aims to see the application of learning videos and Quizzes in increasing students' interest in learning English in the 9th graders. During the learning activities, students first listened to the learning video, then after understanding the material in the video, students were asked to work on practice questions on Quizizz. This study used qualitative descriptive research, with the research subject being the 9th graders. The instrument used is a test instrument in the form of a quiz on the Quizizz application which consists of 15 questions, and interviews as a reference to determine students' understanding and learning interest in the use of learning videos and Quizizz applications. The results showed that the use of learning media using audio-visual media was quite effective in increasing students' interest in learning and understanding English subjects. Because students better understand the material in the form of videos, and also this Quizizz media is not only easy to use but also fun like playing a game. So that students do not feel burdened with assignments. Interactive and fun learning has an impact on increasing student interest in learning.